IMPLEMENTATION OF THE VOCATION SCHOOL OF LEGISLATION AGENCY IN DISCUSSION AND AGREEMENT VILLAGE REGULATION (Study of The Implementation of The Sriwulan Village BPD in Sayung District, Demak Regency) - Siti Rodhiyah Dwi Istinah (Jurnal Pembaharuan Hukum, 2019)
Reform and regional autonomy is actually a new hope for the goverment and village communities to build their villages according to the needs and aspirations of the community.  The implementation of development in the village is intended to improve the standard of living and welfare of the village community itself through the establishment of policies, program activities that are in accordance with the essence of the problem and priority needs of the village community. The Village Consultative Division (BPD in Indonesian) is an institution of the realization pf democracy from the village community or an institution that represents the voice of the community and is a working partner of the village Government in administering The Goverment in the village head along with his device was overseen by the Village Consultative Division (BPD in Indonesian). The method of the approach used in this study is the Juridical  Sociological approach, it uses the Juridical Sociological. The selection results obtained include : 1) Inbiting factors influenced by human resource factors both from the village Government itself as the highest office holder in the village, as well as from PD members who are tasked with assisting in the implementation of the legislative functions of approval and discussion of illage regulations. 2) Solutions and efforts, the village Goernment is expected to conduct training in human resource development such as improving the quality of education and developing capabilities in shapping regulations.